PENERAPAN BAHAN AJAR ELEKTRONIK BERBASIS GOOGLE SITES UNTUK MENINGKATKAN HASIL BELAJAR SISWA - Nurhayati, Nia; Yulianengsih, Neng Lia (Universitas Muria Kudus, 2024)
The aim of this research is to determine the differences between Google Sites before being used and after being used as electronic teaching materials in improving student learning outcomes on plant breeding material.The research method used is a quantitative experimental method with a pre-experimental design. The data collection techniques used were pretest, posttest and documentation. The data analysis technique is an instrument test which consists of validation and reliability tests, distinguishing power and level of difficulty and also uses data tests which consist of normality tests, homogeneity tests and T tests which use parametric statistical tests, namely the paired samples t test.The research results show that electronic teaching materials based on Google sites are successful in use. This can be proven by the calculated results of the paired samples t test on the aspect of learning outcomes which obtained a value of 0.000, where Sig. (2-tailed) 0.05, then the result Ha is accepted. So it can be concluded that Google Sites can be applied as teaching material in elementary schools to improve student learning outcomes.